Computer Graphics, Imaging and Visualisation (CGIV 2007) 2007
DOI: 10.1109/cgiv.2007.33
|View full text |Cite
|
Sign up to set email alerts
|

Decision Fusion Based on Voting Scheme for IR and Visible Face Recognition

Abstract: In this paper we present an evaluation study of decision fusion strategies for infrared (IR) and visible face recognition. Several decision fusion methods based on voting scheme (minimization, product and averaging) are discussed and experiments for various conditions of probe set are performed on two databases with paired IR and visible face imageries. The Eigenfaces and Fisherfaces classification techniques are used to extract the face features and the performance of fusion methods are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Decision-level fusion, where the core idea is to use different classifiers to vote on the final classification result, either by majority voting or by weighted voting. In [21], the method first reduces the dimensionality of the data in the dataset by Fisherfaces, then defines four distance metrics to measure the matching score between the test image and the training image, and finally assigns a weight to each matching score, and obtains the final matching score, i.e., the recognition result, by weighted voting.…”
Section: Feature Fusion Strategiesmentioning
confidence: 99%
“…Decision-level fusion, where the core idea is to use different classifiers to vote on the final classification result, either by majority voting or by weighted voting. In [21], the method first reduces the dimensionality of the data in the dataset by Fisherfaces, then defines four distance metrics to measure the matching score between the test image and the training image, and finally assigns a weight to each matching score, and obtains the final matching score, i.e., the recognition result, by weighted voting.…”
Section: Feature Fusion Strategiesmentioning
confidence: 99%
“…Furthermore, the fusion-based algorithms, both at the image level and the match score level, increased the recognition accuracy by at least 10.2-13.7% . Shahbe et al in [4], proposed a comparative study of several rank-based decision fusion techniques, specifically minimum ranking fusion, product ranking fusion, and average ranking fusion to fuse IR and visible modalities at match score level.The study, applied on the Equinox and OTCBVS databases, has shown a superiority of the average ranking technique over one modality based systems.…”
Section: Introductionmentioning
confidence: 99%